Implementasi Sistem Pemasaran Kenderaan Roda Empat Pada Showroom Pt Armada Banda Jaya - Dedy Andika; Iskandar Zulkarnaini (Jurnal Tika, 2022)
The marketing system that has been used by PT. The Banda Jaya fleet uses cooperation with field agents to market cars. The sales system in this way takes a long time in the process of selling the car, so this system is considered less effective and efficient. If you only rely on the sales system in this way, the company's income will not experience a significant increase. In addition, the development of the company feels considered rather slow. In making sales still use the manual method. Therefore, we need a student attendance system that can collect data and manage data so that it can be done quickly, efficiently and accurately. Making this system is done by collecting data, system analysis, system design, and system implementation. This system is created using the programming language PHP and MySQL for database management. As a result of this thesis, a web-based application is made, a PHP-based promotional information system using the web, which has facilities such as: car data management, sales data management, and sales recap reports. With this application, it is hoped that the car marketing promotion process will be more effective and accurate